Magistério e cultura: a formação cultural dos professores e sua percepção das potencialidades educativas dos museus de arte - Cruz, Livia Lara da (2008)
This report of research has the objective of presenting an analysis of the collected data for the realization of a study that pretends to analyze the existent relations between the cultural formation of the basic school and high school teachers, that work at the public education system of São Paulo, and their perceptions of the art museums education potentiality. Having as main theoretical reference the french sociologist Pierre Bourdie and his concept of cultural capital, i intended to apprehend in which way the cultural formation of the teachers can or not determinate a better relationship with the art museums. For that reason, between the months of september and november of 2007 questionnaires were applied to two groups of distinct teachers considering their social origin, scholar and professional formation, information about habits of leisure, culture and opinion about museums and art exhibitions. The group 1 included twenty teachers, that scheduled spontaneously more than one visit with their students during the year of 2007, having monitorship to the Museu Lasar Segall, seated at the district of Vila Marina ( south area of São Paulo city). The group 2 included another twenty teachers, that scheduled visits to the Museu Lasar Segall having monitorship because of their school s participation at a project financed by the Secretary of Education of the State of São Paulo, and did not come back until the end of 2007. The results permitted to perceive the approximation between the two groups, especially about their social origin, but differences between their relation with the formation institution, the relation kept with state cultural objects and more specifically with the art museum. The teachers of the group 1(spontaneous) declared to have more access, since childhood, to cultural objects such as books, cinema, library and museum. The majority came from public universities of the state of São Paulo, these teachers could tell with more precision the name of the last book that they read or some of theirs favorites plastic artists; and they are also those that access internet more often, have already traveled to other countries and make visits to museums more frequently. The teachers of the group 2(project), whose access to cultural objects since childhood showed to be smaller, were students of private universities (some out of the state of São Paulo), had more difficulties to tell the name of last books that they read or the name of their favorite artists, they do not have access to the internet very often, and never traveled to other countries, and for two of them, the visit to the Museu Lasar Segall was the first visit to a museum. So, the aspect to be observed is to consider which is the importance of the formation institution (the public universities, being more traditional in academic aspects and privates that normally do not receive the same amount of importance in this area) has at the constitution of an habit of frequency at cultural areas; but it is fundamental to consider the importance that family action and, consequently, the cultural habits during the childhood have, the possibilities of them to have access to cultural objects when they are older, and the way that it is made. Considering the interviews that were realized with two teachers of the first group, it was possible to apprehend some strategies developed by families that, even not having much of scholar capital and cultural capital, contributed to an appropriation of the cultural objects for their children, being it to give more importance to the progress in school and what school represents, or being a bridge between a legitimate culture and their children